PENGARUH MEDIA ASSEMBLR EDU BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR IPAS MATERI MENGENAL ORGAN PENCERNAAN MANUSIA DI KELAS V SD NEGERI 101775 SAMPALI T.A 2025/2026 - Monalisa Chaira Nainggola; Suyit Ratno (STKIP Subang, 2026)
This research is motivated by the low learning outcomes of fifth-grade students at SD Negeri 101775 Sampali. The study aims to find out whether there is a significant effect of using assembler edu media based on augmented reality on the topic of Getting to Know the Human Digestive Organs. This research is a quasi-experimental study with a nonequivalent control group design. It used purposive sampling with the research sample consisting of students from SD Negeri 101775 Sampali, namely class VA with 25 students as the experimental class and class VB with 25 students as the control class, making the total sample 50 students. The data collection instrument uses a multiple-choice test, while the data analysis technique uses the t-test (Independent Sample t-test) processed with the help of IBM SPSS Statistics 25 software. The research results show that the learning outcomes of students in the experimental class who received treatment using AR-based Assembler Edu media were higher compared to the learning outcomes of students in the control class who did not receive the treatment. The experimental class had an average pretest score of 59.20, which then increased to 83.00 in the posttest, while the control class had an average pretest score of 64.00, which then increased to 75.40 in the posttest. Hypothesis testing results showed that the significance value (2-tailed) was 0.000, which is < 0.05, so Ho was rejected and H1 was accepted. It can be concluded that AR-based Assembler Edu media significantly affects the science learning outcomes of fifth-grade students at SD Negeri 101775 Sampali.